Recontextualization of Power Symbols in Public Space: The “Tot Tot Wuk Wuk” Phenomenon in Indonesia Through a Multimodal Critical Discourse Analysis Approach - Nehru, Nio Awandha; Nurhayati, Dwi Astuti Wahyu; Suspaningrum, Dewi (Linguistics and ELT Journal, 2025)
This study aims to analyze how symbols of state authority are recontextualized and transformed within digital public spaces through the “Tot Tot Wuk Wuk” phenomenon in Indonesia, employing a Multimodal Critical Discourse Analysis (MCDA) approach and a constructive qualitative methodology with Genre and Multimodal (GeM) analysis design. The phenomenon illustrates the appropriation of state authority symbols, such as strobe lights, sirens, and imitation license plates by civilians without official authorization. These acts not only constitute legal violations but also serve as social expressions of status and prestige. Drawing on Theo van Leeuwen’s framework of social actor representation and recontextualization, as well as Kress and van Leeuwen’s concept of social modality, this research analyzes visual, verbal, and legal modes across various online media texts, digital images, and viral social media videos. Using a constructive qualitative methodology, the study goes beyond mere description to interpret the social and ideological meanings underlying these symbolic practices, integrating the researcher’s reflective interpretation as the primary analytical instrument. The findings reveal that the “Tot Tot Wuk Wuk” phenomenon operates as a multimodal discourse interlinking legality, morality, and the performativity of power. Symbols of authority are recontextualized into tools of social identity expression, signifying status disparities and the desire for symbolic legitimacy within public spaces. However, this study is limited by its reliance on secondary data, which constrains deeper validation of audience perceptions and real-world behavioral impacts related to the “Tot Tot Wuk Wuk” phenomenon